Fixation of lung apex in spontaneous pneumothorax is safe and efficient in decrease recurrences - Wendy Yang; Pei-Yeh Chang; Ai-Hua Yeh; Yung-Ching Ming; Jeng Chang Chen; Jin-Yao Lai (Pediatrics and Neonatology)
Background: Video-assisted thoracoscopic bullectomy with pleurodesis is widely used to treat spontaneous pneumothorax. However, 1%–3% of patients experience postoperative complications that may require reoperation, such as bleeding or prolonged air leaks, and 3%–7% of patients require a repeat thoracoscopic bullectomy due to recurrence. Therefore, a modified procedure with improved outcomes is required. Methods: Between January 1, 2011 and December 31, 2015, 196 patients with spontaneous pneumothorax underwent thoracoscopic bullectomy and pleurodesis with or without fixation of the lung apex to the chest wall. In patients in the fixation group, the lung apex was fixed to the chest wall with two non-absorbable sutures after bullectomy and pleurodesis. The treatment of each lung was considered an independent operation in patients with bilateral spontaneous pneumothorax. Results: The patients in each group had comparable backgrounds. In the fixation group, 67 patients underwent 87 operations, four of which (in three patients) led to recurrences (recurrence rate, 4.60%). There were no readmissions or reoperations within 30 days in this group. In the non-fixation group, 128 patients underwent 161 operations, 14 of which (in nine patients) led to recurrences (recurrence rate, 8.7%). In addition, three patients in this group required reoperation and two were readmitted within 30 days. Conclusions: Modified thoracoscopic bullectomy with fixation of the lung apex is a safe procedure that provides better outcomes with lower complication rates. Key Words: spontaneous pneumothorax, thoracoscopic bullectomy, video-assisted thoracoscopic surgery (VATS), lung apex fixation